Peraturan Daerah Bernuansa Syari’ah Dan Hubungannya Dengan Pelaksanaan Tugas Serta Kewajiban Pemerintah Daerah - Nuvazria Achir; Sri Nanang Meiske Kamba (Universitas Medan Area, 2020)
This study aims to analyze local regulations with syari'ah nuances and their relationship with the implementation of local government duties and obligations. The method used in this research is normative juridical using a descriptive analytical approach. The results show that: Regional Autonomy in principle hands over authority to local governments to regulate and manage their territories, including in the preparation of legal products. Perda Syari'ah is drafted as an arrangement for the ins and outs of one's worship, and is also related to social interaction in the community which is called the Muamalah aspect. In this regard, of course this is part of the mandatory affairs of which the regional government is carried out based on the concurrent authority as contained in Article 11 and Article 12 of Law Number 23 of 2014, as well as Article 7 of Government Regulation (PP) Number 38 of 2007. In relation to regional autonomy, the power to manage and regulate the regions becomes the duties and responsibilities given by law and is even contained in the contents of the constitution, the aim is to facilitate the task of the regional head in handling social affairs. Therefore, it is important to respect the traditional rights of the region including the regional regulations with the content of Shari'ah as contained in Article 18A Paragraph (1) and Article 18B Paragraph (1), as well as Paragraph (2) of the 1945 Constitution of the Republic of Indonesia, and simplify religious affairs which are regional rights within the framework of service to the basic needs of the community